Cyclic AMP and low molecular weight effector(s) present in yeast extract are involved in pectin lyase production by Penicillium griseoroseum cultured on sucrose - Pereira, Maria Cristina Baracat-; Coelho, Jorge Luiz Cavalcante; Minussi, Rosana Cristina; Alves, Virgínia Maria Chaves; Brandão, Rogelio Lopes; Silva, Daison Olzany (Applied Biochemistry and Biotechnology, 1999)
Pectin lyase (PL) induction by organic and inorganic components of yeast extract (YE) was evaluated in Penicillum griseoroseum, cultured in a mineral medium containing sucrose, by determining PL activity (A 235) and mycelial growth (mycelial dry weight). The lowest YE concentration that promoted significant PL induction without acting as a carbon source for the fungus corresponded to 0.0075%. Neither calcined YE nor a nutrient solution containing micronutrients induced PL production, indicating that the inducer was an organic compound. Vitamins, phospholipid components, amino acids, and nitrogenous bases were tested in place of YE and promoted no significant PL induction. APL inducer compound was found to be soluble in the nucleotide fraction obtained during extraction of YE. The inducer was shown to be a thermostable polar substance dialyzable at 2000 Daltons, hydrolyzable by HCl, and activated by boiling for up to 60 min. Cyclic AMP (cAMP) exogenously added to the culture medium at 5 and 10 mM was capable of inducing PL in P. griseoroseum grown on sucrose, suggesting that at least one compound may be present in YE acting in a cooperative fashion for the maintenance of high levels of cAMP in to the cell. PL activity and the level of cAMP inside the fungal cells increased after the addition of YE to the culture medium, suggesting the participation of this messenger in this enzyme's synthesis.
Keywords: Cyclic AMP; Yeast extract; Pectin lyase; Pectinases; P. griseoroseum; Sucrose